CT enteroclysis/enterography findings in drug-induced small-bowel damage - Kishi, T (Br J Radiol, 2014)
OBJECTIVE: To evaluate the CT enteroclysis (CTE)/enterography findings of patients with small-bowel mucosal damage induced by aspirin or non-steroidal anti-inflammatory drugs (NSAIDs) and to compare these findings with the duration of drug use and endoscopic findings. METHODS: CTE findings of 11 patients (22 lesions) with drug-induced small-bowel damage were reviewed, including 8 NSAID users and 3 aspirin users. Three patients were short-term users (6 months or shorter) and eight were long-term users (3 years or longer). Nine patients also underwent videocapsule endoscopy (VCE) or double-balloon enteroscopy (DBE). RESULTS: Small-bowel abnormalities were visible in 8 of 11 patients (73%) on CTE. Multiple lesions were seen in five patients, including all short-term users. Lesions were classified into three types. Type 1 (mucosal patchy enhancement) was found in four of eight patients (50%, 12 lesions) all were short-term users. Small erosions with mild oedema/redness were shown by DBE. Type 2 (homogeneous hyperenhancement) was found in two of eight patients (25%, four lesions) who were long-term users. Large ulcers with marked oedema/redness were shown by DBE. Type 3 (stratification enhancement) was found in four of eight patients (50%, six lesions), both short-term and long-term users. Annular or large ulcers with strictures were shown by VCE or DBE. CONCLUSION: On CTE, Type 1 lesions in patients with mostly short-term aspirin or NSAID use, Type 2 lesions in patients with long-term use and Type 3 lesions in both types of patients were detected. CTE may have usefulness for the detection of mild damage. ADVANCES IN KNOWLEDGE: Small-bowel abnormalities owing to aspirin or NSAID present with three different patterns on CTE.